Micropropagação e conservação in vitro de bromeliáceas - Garcia, Fabio Ribeiro (2013)
bromeliad species are native to Brazil and have great potential for use as an ornamental plant, and a relevant ecological importance. Considering the devastation of the Atlantic, currently 7.3% of its original area preserved and where about 70% are endemic bromeliad is important to establish methods of propagation and ex situ conservation in order to preserve this germplasm and avoid irreversible genetic erosion. Thus, the aim of this work was to establish protocols and micropropagation in vitro conservation of A. blancheteana and A. miniata. In the first chapter, for multiplication in vitro, we used different concentrations of BAP and for rooting tested different concentrations of auxins IAA, IBA and NAA. In the second chapter we tested two protocols, was first used in MS medium supplemented with different concentrations of auxin Picloram and 2,4-D combined with BAP and the second experiment evaluated MS medium supplemented with 2,4-D or picloram in different concentrations. In the third chapter, we investigated the effect of osmotic agents, sucrose, sorbitol and mannitol in vitro conservation A. blancheteana. For the best result micropropagation for multiplication was for medium supplemented with 4.44 μM BA. To induce somatic embryos and regeneration of the concentration of 22.5 μM 2,4-D was the most efficient. Independent of concentration, mannitol was more efficient for in vitro conservation of A. blancheteana for 12 months.